Entanglement entropy of local operators in quantum Lifshitz theory. (29th September 2016) - Zhou, Tianci
Abstract: We study the growth of entanglement entropy (EE) of local operator excitation in the quantum Lifshitz model with dynamic exponent z = 2. Specifically, we apply a local vertex operator to the groundstate at a distance l to the entanglement cut and calculate the EE as a function of time for the state's subsequent time evolution. We find that the excess EE compared with the groundstate is a monotonically increasing function which is vanishingly small before the onset at t ∼ l 2 and eventually saturates at a constant value proportional to the scaling dimension of the vertex operator. The quasi-particle picture can interpret the final saturation as the exhaustion of the quasi-particle pairs, while the diffusive nature of the time scale t ∼ l 2 replaces the common causality constraint in CFT calculations. To further understand this property, we compute the excess EE of a small disk probe far from the excitation point and find chromatography patterns in EE generated by quasi-particles of different propagation speeds.